Comparative Analysis of the Social Responsibility of Universities in the UK and Kazakhstan - Kaldybay, Kainar; Sanat, Kumarbekuly; Aitenov, Zhasulan; Koishina, Akmaral; Kelgembayeva, Bakytzhan; Kassymbek, Aliya (Journal of Ecohumanism, 2024)
The scientific project addresses the issue of social responsibility of Kazakhstani and British universities. It is not for nothing that today the social responsibility of universities is seen as the third mission after education and research. We believe that this is a reflection of the growing influence of universities on the development of society and states, and, most importantly, an increase in requirements for the quality of Education. On this issue, a comparative analysis of the medium and long-term development strategies, plans and other current regulations of universities selected as case studies was carried out using a content analysis approach. Interviews were conducted with persons involved in these educational institutions and a review of the practical implementation of the University's social responsibility was conducted. The analysis shows that in the documents outlined by the goals of some Kazakhstani universities today little attention is paid to many aspects of Social Responsibility, whereas in some, on the contrary, there is a high experience of implementing social responsibility through the institutionalization of UNESCO Sustianable Development Goals set out in the document "transforming the world: on the agenda in the field of sustainable development until 2030" (UNESCO 2015.